EFFECT OF NEUROPROTECTIVE THERAPY WITH CITICOLINE ON THE COURSE OF EXPERIMENTAL NON-INFECTIOUS ANTERIOR AND INTERMEDIATE UVEITIS - Zborovska, O.V.; Horіanova, I.S.; Ulianov, V.O.; Dorokhova, O.E.; Maltsev, E.V.; Molchaniuk, N.I. (World of Medicine and Biology, 2024)
Non-infectious anterior and middle uveitis is a significant uveitis group, leading to decreased visual acuity and often blindness. The purpose of the study was to determine the features of the clinical course and morphological changes of the choroid, retina, and optic nerve in the early and late stages of experimental non-infectious anterior and middle uveitis under the conditions of neuroprotective citicoline therapy. We studied the clinical course of the disease and morphological changes on the 10–13th, and 33rd days after the administration of the provocative dose. The use of citicoline led to a decrease in inflammation in uveitis. First of all, due to reduced swelling of the cornea and iris. It was confirmed by histomorphological examination. It reduced the violation of the retinal cytoarchitectonic disturbances and degenerative and destructive changes in its neurons. It also reduced the swelling of the retina and optic nerve cells. It activated intracellular compensatory processes in the retina, particularly in the pigment epithelium and optic nerve glial cells.
Keywords: anterior uveitis; intermediate uveitis; experimental animal model; choroid; retina; optic nerve; citicoline